An Overview of Patient-reported Outcomes for Men with Prostate Cancer: Results from the PIONEER Consortium - Sebastiaan Remmers; Katharina Beyer; Tariq A. Lalmahomed; Peter Prinsen; Nicole J.E. Horevoorts; Nora Tabea Sibert; Christoph Kowalski; Francesco Barletta; Oliver Brunckhorst; Giorgio Gandaglia; Jochem R.N. van der Voort van Zyp; Emma J. Smith; et al. (European Urology Open Science)
Background and objective: Patient-reported outcome measures (PROMs) are increasingly being used to capture the patients’ perspective of their functional status and quality of life (QoL). Big data can help us better understand patient-reported outcomes (PROs). Using prospectively collected data from the Prostate Cancer Diagnosis and Treatment Enhancement Through the Power of Big Data in Europe (PIONEER) consortium, we aimed to describe the functional status and QoL in men with prostate cancer (PCa) treated with active surveillance (AS), radical prostatectomy (RP), and radiotherapy (RT), and to demonstrate the applicability of PROM data on a large scale and at a European level. Methods: We identified data sources that collected QoL data using the European Organization for Research and Treatment of Cancer (EORTC) QLQ-C30, EORTC QLQ-PR25, or Expanded Prostate Cancer Index Composite (EPIC)-26/50 questionnaires. Aggregated summary scores for urinary, bowel, and sexual dysfunction, global health status, and QoL were shared for each data source. Key findings and limitations: We identified eight data sources originating from various settings: routine hospital data, embedded research PRO collection, survey data collected by a patient organization, multi-institutional prospective cohort study, and registry data. PRO data were available for 709 men on AS, 20 508 on RP, and 3417 on RT, with a median time between diagnosis and PROM assessment ranging from 1 to 8.7 yr. Most men were diagnosed with Gleason ≤7 disease, and T1 or T2 PCa. We observed that sexual dysfunction was the most affected PRO and found large differences between data sources. Conclusions and clinical implications: Our results support the feasibility of PRO assessment using big data in Europe. Implementation of PROMs in clinical practice and the use of standardized methods could improve value-based health care provision. Patient summary: In this study, we combined several data sources that reported urinary, bowel, and sexual dysfunction, global health status, and quality of life. We identified eight data sources and show that sexual function is the most affected domain after treatment.